Russia and India : As Close As Lips & Teeth? - Cheang, Chris (2018)
President Vladimir Putin’s visit to India on 4-5 October 2018 for the 19th annual bilateral summit saw the signing of a major weapons system. This served relatively well Russia’s domestic and foreign policy objectives.